MODELING STUDIES ON DICENTRICS INDUCTION AFTER SUB-MICROMETER FOCUSED ION BEAM GRID IRRADIATION. Issue 1 (17th December 2018) - Friedland, W; Kundrát, P; Schmitt, E; Becker, J; Ilicic, K; Greubel, C; Reindl, J; Siebenwirth, C; Schmid, T E; Dollinger, G
Abstract: The biophysical simulation tool PARTRAC contains modules for DNA damage response representing non-homologous end joining of DNA double-strand breaks (DSB) and the formation of chromosomal aberrations. Individual DNA ends from the induced DSB are followed regarding both their enzymatic processing and spatial mobility, as is needed for chromosome aberrations to arise via ligating broken ends from different chromosomes. In particular, by tracking the genomic locations of the ligated fragments and the positions of centromeres, the induction of dicentrics can be modeled. In recent experiments, the impact of spatial clustering of DNA damage on dicentric yields has been assessed in AL human-hamster hybrid cells: Defined numbers of 20 MeV protons (linear energy transfer, LET 2.6 keV/μm), 45 MeV Li ions (60 keV/μm) and 55 MeV C ions (310 keV/μm) focused to sub-μm spot sizes were applied with the ion microbeam SNAKE in diverse grid modes, keeping the absorbed dose constant. The impact of the μm-scaled spatial distribution of DSB (focusing effect) has thus been separated from nm-scaled DSB complexity (LET effect). The data provide a unique benchmark for the model calculations. Model and parameter refinements are described that enabled the simulations to largely reproduce both the LET-dependence and the focusing effect as well as the usual biphasic rejoining kinetics. The predictive power of the refined model has been benchmarked against dicentric yields for photon irradiation.